Upswing in a subdued global economy: DIW economic outlook - Ferdinand Fichtner; Guido Baldi; Franziska Bremus; Karl Brenke; Christian Dreger; Hella Engerer; Christoph Große Steffen; Simon Junker; Claus Michelsen; Katharina Pijnenburg; Maximilian Podstawski; Malte Rieth; et al. (DIW Economic Bulletin, 2015)
The German economy continues to recover, and will grow by 2.2 percent in 2015 and by 1.9 percent in 2016. The unemployment rate will further decline, to 6.4 percent this year and 6.1percent in 2016. Inflation, which averages 0.5 percent this year, will be substantially dampened by the slump in oil prices; in 2016 as well, inflation will remain low, at 1.2 percent. The global economy continues in its recovery. In industrialized countries, a gradually improving situation in labor markets, as well as the slump in oil prices, is propelling the purchasing power of private consumers. Corporate investment activity should also pick up, benefitting from easy monetary policy. In many economies in the euro area, unemployment remains high and the public and private debt is dampening demand. For the time being, growth in the emerging markets is expected to lag behind. Overall, the average annual growth rate of the global economy is expected to be 3.8 percent in 2015, and 4.0 percent in the following year. The German economy is currently recovering, driven by strong domestic demand, and should be back on its potential path later on. Inflation is bound to remain weak. There is no sign of the German economy overheating; important markets have lost momentum when compared to the pre-crisis years - foreign trade is therefore likely to provide only minor stimulus, and in this environment, investments in equipment and machinery will only experiencea moderate expansion. Government revenues are surging: despite a rather loose spending behavior, the public budget surpluses will reach approximately 0.5 percent in both years of the forecast period.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook